Pengaruh media sosial terhadap kesejahteraan emosi remaja: Tantangan dan strategi pengelolaan - Tamami, Abi Syamsudin (Maliki Interdisciplinary Journal, 2024)
Social media has changed the pattern of social interaction of adolescents, bringing a complex impact on their emotional well-being. This article explores the psychological impact of social media use on adolescents, identifies emerging challenges, and proposes management strategies that have the potential to help overcome negative impacts. Through an analysis of the literature and empirical studies, we illustrate how social media can provide social connectedness and support, but can also stimulate adverse social comparisons and feelings of inferiority. Challenges such as difficulty moderating use and anxiety of missing out on information are also discussed, highlighting the possible negative influences. However, this article does not only describe the problem, but also proposes solutions that can be referred to. We propose a strong digital literacy approach to empower youth in coping with social media, as well as setting wise screen time limits. In addition, we encourage direct social interaction and participation in activities outside of social media as important strategies for maintaining emotional well-being. As such, this article presents a holistic view of the influence of social media on adolescents, proposing management strategies that have the potential to help them maintain emotional well-being in this digital age.